Engineering materials 2 : an introduction to microstructures and processing - Ashby, M. F. (International series on materials science and technology., 2013)
Engineering Materials 2 is one of the leading self-contained texts for more advanced students of materials science and mechanical engineering. The book provides a concise introduction to the microstructures and processing of materials and shows how these are related to the properties required in engineering design. As with previous editions, each chapter is designed to provide the content of one 50-minute lecture. The fourth edition has been updated to include new case studies, more worked examples, links to relevant websites and video clips. Other changes include an increased.